A longitudinal database of Irish political speech with annotations of speaker ability. - Cullen, Ailbhe; Harte, Naomi (Language Resources & Evaluation, 2018)
This paper presents the Irish Political Speech Database, an English-language database collected from Irish political recordings. The database is collected with automated indexing and content retrieval in mind, and thus is gathered from real-world recordings (such as television interviews and election rallies) which represent the nature and quality of recordings which will be encountered in practical applications. The database is labelled for six speaker attributes: boring; charismatic; enthusiastic; inspiring; likeable; and persuasive. Each of these traits is linked to the perceived ability or appeal of the speaker, and as such are relevant to a range of content retrieval and speech analysis tasks. The six base attributes are combined to form a metric of Overall Speaker Appeal. A set of baseline experiments is presented, which demonstrate the potential of this database for affective computing studies. Classification accuracies of up to 76% are achieved, with little feature or system optimisation.